Introduction - money is only half of the story - Pohlmann, Markus (Bribery, fraud, cheating, 2020)
Scandals never stop. From Siemens to VW and Petrobras, from FIFA to the DFB—in Germany as well as in other countries—it is the large, renowned companies, clinics, associations and parties that come into the limelight because of their illegal activities with sometimes severe consequences. It is striking that a wide range of areas from economy to politics, from medicine to sports have been affected.
Gesehen am 05.12.2022